2003
DOI: 10.1021/ja029135q
|View full text |Cite
|
Sign up to set email alerts
|

Photodissociation of the Phosphine-Substituted Transition Metal Carbonyl Complexes Cr(CO)5L and Fe(CO)4L:  A Theoretical Study

Abstract: The photochemistry of the phosphine-substituted transition metal carbonyl complexes Cr(CO)(5)PH(3) and ax-Fe(CO)(4)PH(3) is studied with time-dependent DFT theory to explore the propensity of the excited molecules to expel their ligands. The influence of the PH(3) ligand on the properties of these complexes is compared with the photodissociation behavior of the binary carbonyl complexes Cr(CO)(6) and Fe(CO)(5). The lowest excited states of Cr(CO)(5)PH(3) are metal-to-ligand charge transfer (MLCT) states, of wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
4
3
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(30 citation statements)
references
References 54 publications
0
30
0
Order By: Relevance
“…All calculations indicate that the excited Cr(CO)5L molecules (L = PH3, PC2H5, and PCH3) prefer dissociation of their phosphorus substituent over that of an CO ligand ( Figure 7). This suggests that the photochemical approach may be a viable complement to the ligand exchange and redox methods that are currently employed to demetalate transition metal complexed organophosphorus compounds [87]. …”
Section: Scheme 20mentioning
confidence: 99%
“…All calculations indicate that the excited Cr(CO)5L molecules (L = PH3, PC2H5, and PCH3) prefer dissociation of their phosphorus substituent over that of an CO ligand ( Figure 7). This suggests that the photochemical approach may be a viable complement to the ligand exchange and redox methods that are currently employed to demetalate transition metal complexed organophosphorus compounds [87]. …”
Section: Scheme 20mentioning
confidence: 99%
“…In [Cr(CO) 5 (PH 3 )], PECs calculated with TD-DFT showed that avoided crossings with higherlying 1 LF states render low-lying 1 MLCT states dissociative along the Cr−PH 3 coordinate, whereas energy barriers arise along the Cr−CO coordinates [14].…”
Section: Metal Carbonyl Complexes (A) Photochemistry Of Metal Carbonymentioning
confidence: 99%
“…For example, MLCT states were identified as the lowest states in [Cr(CO) 5 (PH 3 )] [14], [W(CO) 5 (4-cyanopyridine)] and [W(CO) 5 (piperidine)] [15].…”
Section: Metal Carbonyl Complexes (A) Photochemistry Of Metal Carbonymentioning
confidence: 99%
“…Wernet et al [22], vibrational modes were obtained at the DFT/B3LYP/cc-pVDZ level of theory using the MOLPRO package, interfaced to SHARC has been used [32]. We also checked the variation of geometry at DFT level of theory and found that cam-B3LYP which is used for ESMD in this study and TPSSH which is often the best functional for transition metal system predicts very similar geometry to the CASPT2 (12,12) geometry.…”
Section: Discussionmentioning
confidence: 75%